An anti-dengue and anti-herpetic polysulfated fraction isolated from the coenocytic green seaweed Caulerpa cupressoides inhibits thrombin generation in vitro - Rodrigues, José Ariévilo Gurgel; Eloy, Ygor Raphael Gomes; Vanderlei, Edfranck de Souza Oliveira; Cavalcante, Jéssica Figueiredo; Romanos, Maria Tereza Villela; Benevides, Norma Maria Barros (Acta Scientiarum. Biological Sciences, 2017)